Islamic morals in financial transactions and their impact on peaceful coexistence - Abdulkareem hameed Al-jhayyish, Basim (International Journal of Psychosocial Rehabilitation, 2020)
All parts of the world today witness many forms of intolerance, extremism, and moving away from the ideal and moral values, for the purpose of achieving material interests by all legitimate and unlawful means. The goal of this humble research is to recall some ethical principles in the financial dealings of the true Islamic religion because of its impact on peaceful coexistence, many rumors teach about it.